Nebulized Ketamine for Analgesia in the Prehospital Setting: A Case Series. (17th February 2023) - Patrick, Casey; Smith, Michael; Rafique, Zubaid; Rogers Keene, Kelly; De La Rosa, Xavier
Abstract: We report the initial seven patients treated with nebulized ketamine for moderate to severe pain, via breath-actuated nebulizer, in an urban, ground-based emergency medical services (EMS) system. Ketamine for analgesia in the emergency setting has become widespread over the past decade. The addition of a non-parenteral, inexpensive, and well-tolerated ketamine delivery option is extremely desirable. We believe these initial data demonstrate promising pain reduction coupled with minimal side effects, indicating a potential role for nebulized ketamine in EMS.